2007
DOI: 10.1111/j.1463-5224.2007.00564.x
|View full text |Cite
|
Sign up to set email alerts
|

Ganglion cell death in glaucoma: from mice to men

Abstract: Glaucoma results from the degeneration of retinal ganglion cells and their axons. Over the last 20 years several important advancements have been made in our understanding of the molecular pathology of this disease, particularly through the development of rat models of experimental glaucoma and the characterization of a spontaneous secondary form of glaucoma in DBA/2 substrains of inbred mice. One of these advances is the observation that ganglion cells die by apoptosis, an intrinsic molecular pathway of progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 73 publications
0
38
0
1
Order By: Relevance
“…46 Skarie and Link 92 showed that at the cellular level, loss of Wdr36 disrupts ribosomal RNA maturation and leads to nucleolar morphology defects, resulting in activation of the p53 stress-response pathway. In POAG, it is established that RGCs are lost because of apoptosis 93,94 and p53 is a key regulator of the apoptotic pathway. Their data showing an interaction of p53 and WDR36 suggest that variants in these genes could potentially synergize in POAG pathogenesis.…”
Section: Wdr36 At the Glc1g Locusmentioning
confidence: 99%
“…46 Skarie and Link 92 showed that at the cellular level, loss of Wdr36 disrupts ribosomal RNA maturation and leads to nucleolar morphology defects, resulting in activation of the p53 stress-response pathway. In POAG, it is established that RGCs are lost because of apoptosis 93,94 and p53 is a key regulator of the apoptotic pathway. Their data showing an interaction of p53 and WDR36 suggest that variants in these genes could potentially synergize in POAG pathogenesis.…”
Section: Wdr36 At the Glc1g Locusmentioning
confidence: 99%
“…The primary stage is described as the "elevation of IOP and the activation of optic nerve glia in the lamina cribrosa" and includes disruption of both retrograde and anterograde axonal transport, including neurotrophins and motor proteins. The research presented here is intended to contribute to our knowledge of stage 1 of this disease, the "activation of the optic nerve glia in the lamina cribrosa" (7).…”
mentioning
confidence: 99%
“…Eye diseases, such as age-related macular degeneration (AMD), 1 retinitis pigmentosa (RP), 2 diabetic retinopathy, 3,4 and glaucoma 5,6 can produce retinal neural dysfunctions that lead to severe vision loss if appropriate interventions are not involved promptly. It is known that different eye diseases damage different retinal cells, which are located in different functional layers.…”
Section: Introductionmentioning
confidence: 99%
“…For example, retinal photoreceptors are vulnerable in AMD 1 and ganglion cells are affected in glaucoma. 6 Electroretinography (ERG) 7 and multifocal ERG 8,9 can provide objective evaluation of retinal neural dysfunction, but the spatial resolution is limited due to the integral effect of bioelectric signals from multiple retinal layers. Each hexagonal stimulus pattern used in multifocal ERG usually has an angular size of ∼5 deg, 8,9 corresponding to ∼2-mm resolution in the human retina.…”
Section: Introductionmentioning
confidence: 99%